Macrophage-specific FGFR1 deletion alleviates high-fat-diet-induced liver inflammation by inhibiting the MAPKs/TNF pathways - Zhao Yan-ni; Liu Zhou-di; Yan Tao; Xu Ting-xin; Jin Tian-yang; Jiang Yong-sheng; Zuo Wei; Lee Kwang Youl; Huang Li-jiang; Wang Yi (Acta Pharmacologica Sinica; Vol 45, No 5 (May 2024): Acta Pharmacologica Sinica, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a common metabolic disease that is substantially associated with obesity-induced chronic inflammation. Macrophage activation and macrophage-medicated inflammation play crucial roles in the development and progression of NAFLD. Furthermore, fibroblast growth factor receptor 1 (FGFR1) has been shown to be essentially involved in macrophage activation. This study investigated the role of FGFR1 in the NAFLD pathogenesis and indicated that a high-fat diet (HFD) increased p-FGFR1 levels in the mouse liver, which is associated with increased macrophage infiltration. In addition, macrophage-specific FGFR1 knockout or administration of FGFR1 inhibitor markedly protected the liver from HFD-induced lipid accumulation, fibrosis, and inflammatory responses. The mechanistic study showed that macrophage-specific FGFR1 knockout alleviated HFD-induced liver inflammation by suppressing the activation of MAPKs and TNF signaling pathways and reduced fat deposition in hepatocytes, thereby inhibiting the activation of hepatic stellate cells. In conclusion, the results of this research revealed that FGFR1 could protect the liver of HFD-fed mice by inhibiting MAPKs/TNF-mediated inflammatory responses in macrophages. Therefore, FGFR1 can be employed as a target to prevent the development and progression of NAFLD.